Ejecución del Plan Anual de Contratación del GAD Parroquial Rural de Ricaurte - Villavicencio Carpio, Fernando Francisco (2019)
In this way the Autonomous Decentralized Rural Parochial Government of Ricaurte has to have all the appropriate procedures to implement the works, for this reason it has to have a control when estimating the costs to execute the project. And to be with all the responsibility and the time and term to present said information and upload it to the digital platform for the proper functioning of their due contracts, and not have any inconvenience when assigning the financial cost, so that it does not cause a disappointment in the inhabitants of said sector where said work will be implemented. Due to the lack of technical study in the parish meeting of Ricaurte, when estimating the costs, this causes it to have complications for the execution of the work and there is a financial increase. Therefore, it is recommended that the president of the Parish Board incorporate procedures that allow for adequate control to satisfy the community of Ricaurte